Research of heat and mass transfer processes in conditions of microwave heating of wet wood; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Kostoreva A. A. Anastasiya Andreevna; Kostoreva Zh. A. Zhanna Andreevna; Rogovaya L. V. Lidiya; Loginov V. S. Vladimir Stepanovich (2017, 2017)
Title screen